Fornix Structural Connectivity and Allostatic Load: Empirical Evidence From Schizophrenia Patients and Healthy Controls. Issue 7 (September 2017) - Savransky, Anya; Chiappelli, Joshua; Rowland, Laura M.; Wisner, Krista; Shukla, Dinesh K.; Kochunov, Peter; Hong, L. Elliot
ABSTRACT: Objective: The fornix is a white matter tract carrying the fibers connecting the hippocampus and the hypothalamus, two essential stress-regulatory structures of the brain. We tested the hypothesis that allostatic load (AL), derived from a battery of peripheral biomarkers indexing the cumulative effects of stress, is associated with abnormalities in brain white matter microstructure, especially the fornix, and that higher AL may help explain the white matter abnormalities in schizophrenia. Methods: Using 13 predefined biomarkers, we tested AL in 44 schizophrenic patients and 33 healthy controls. Diffusion tensor imaging was used to obtain fractional anisotropy (FA) values of the fornix and other white matter tracts. Results: AL scores were significantly elevated in patients compared with controls ( F (3, 77) = 7.87, p = .006). AL was significantly and inversely correlated with FA of fornix in both controls ( r = −.58, p = .001) and patients ( r = −.36, p = .023). Several nominally significant ( p < .05 but did not survive Bonferroni correction for multiple comparison) correlations were also observed between AL and FA of other white matter tracts in schizophrenic patients. However, the fornix was the only tract exhibiting a correlation with AL in both groups. Conclusions: These results provide initial evidence that allostatic processes are linked to fornix microstructure in clinical participants.